Queueing Theory and Network Applications - van Do, Tien.; Takahashi, Yutaka; Yue, Wuyi.; Nguyen, Viet-Ha.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The 16 papers of this proceedings have been selected from the submissions to the 10th  International Conference on Queueing Theory and Network Applications (QTNA2015) held on 17-20 August, 2015 in Ha Noi and Ha Long, Vietnam. All contributions discuss theoretical and practical issues connected with queueing theory and its applications in networks and other related fields. The book brings together researchers, scientists and practitioners from the world and offers an open forum to share the latest important research accomplishments and challenging problems in the area of queueing theory and network applications.
Part I. Queueing Models I -- Part II. Queueing Applications -- Part III. Queueing Models II -- Part IV. Network Models.
Keywords: Computational intelligence; Artificial intelligence; Application software; Operations research; Computational Intelligence; Artificial Intelligence; Computer and Information Systems Applications; Operations Research and Decision Theory